2019
DOI: 10.1038/s41598-019-47655-x
|View full text |Cite
|
Sign up to set email alerts
|

Cells´ Flow and Immune Cell Priming under alternating g-forces in Parabolic Flight

Abstract: Gravitational stress in general and microgravity (µg) in particular are regarded as major stress factors responsible for immune system dysfunction in space. To assess the effects of alternating µg and hypergravity (hyper-g) on immune cells, the attachment of peripheral blood mononuclear cells (PBMCs) to adhesion molecules under flow conditions and the antigen-induced immune activation in whole blood were investigated in parabolic flight (PF). In contrast to hyper-g (1.8 g) and control conditions (1 g), flow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 . Moreover, cell studies in simulated (s-) µ g at ground-based facilities are included in this Collection 2630 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 . Moreover, cell studies in simulated (s-) µ g at ground-based facilities are included in this Collection 2630 .…”
mentioning
confidence: 99%
“…A PF study examined the attachment of peripheral blood mononuclear cells to adhesion molecules under flow conditions, and antigen-induced immune activation in whole blood 25 . The flow and rolling speed of cells were moderately accelerated during µ g periods, which were accompanied by a clear reduction in rolling rate.…”
mentioning
confidence: 99%
“…In addition, after short-duration spaceflight, the peripheral monocytes from astronauts showed no change in the number of cells but a significantly reduced expression of CD26L and major histocompatibility complex, class II, DR (HLA-DR), which are known regulators of cell adhesion between lymphocyte and endothelial cells [71]. Consistent with this finding, the ability of peripheral blood mononuclear cells to adhere to the ICAM-1 substrate was reduced under simulated microgravity and shear flow conditions in vitro [72]. Although the force from the blood flow plays a decisive role in the monocyte's adhesion cascade and initial capture with endothelial by selectins [73], the adhesion ability of immune cells and endothelial cells can also be impaired in microgravity.…”
Section: Microgravity Regulates Adhesion and Activation Of Immune Cellsmentioning
confidence: 66%
“…Previous studies have indicated the changes in monocyte physiology during spaceflight, where it has been found that monocytes lose their ability to trap bacteria after 5 days under microgravity [36]. The effect of immunosuppression with respect to monocytes was confirmed by a later study, where it was found that circulating monocytes lost their ability to invoke an immune response after a parabolic flight, with alternating gravitational forces [37]. While monocytes presented activation markers under hypergravity and normal gravity it manifested immunosuppression-related surface markers [37].…”
Section: Gravity and The Immune Systemmentioning
confidence: 81%